Optically transparent, ultra-tough, aerosol-sprayable, waterborne polyurethane composite reinforced with natural polymer nanofibers. (December 2022) - Jang, Seyeon; Go, Eun Min; Kim, Joong-Kwon; Kwak, Sang Kyu; Jin, Jungho
Abstract: In this study, we introduce an optically transparent, mechanically tough waterborne polyurethane (WPU) nanocomposite incorporating succinylated cellulose nanofibers (SCNF) and chitin nanofibers (SChNF) as the reinforcing fillers. Both a commercially available WPU as well as a typical anionic WPU synthesized using poly(tetrahydrofuran) (PTMEG), isophorone diisocyanate (IPDI), and dimethylol propionic acid (DMPA) as the internal emulsifier are used. Aqueous colloidal suspensions of the SC(h)NF nanofillers are prepared via the aqueous counter collision (ACC) method. A simple blending of the two waterborne materials renders homogeneous WPU/SC(h)NF (1–10 wt%) nanocomposite that simultaneously achieve an outstanding mechanical toughness and high optical transparency (>90%). We also demonstrate an environmentally benign aerosol-spray coating of the WPU/SC(h)NF using dimethyl ether (DME) as the aerosol propellant. Graphical abstract: Image 1 Highlights: Optically transparent and high toughness WPU nanocomposite film is introduced. Cellulose nanofibers and chitin nanofibers are used as reinforcements to WPU. The WPU nanocomposite can be transparently coated using DME as an aerosol propellant.